Simultaneous photocatalytic reduction of hexavalent chromium and oxidation of p-cresol over AgO decorated on fibrous silica zirconia. (15th September 2021) - Aziz, F.F.A.; Jalil, A.A.; Hassan, N.S.; Fauzi, A.A.; Azami, M.S.
Abstract: The co-existence of heavy metals and organic compounds including Cr(VI) and p -cresol ( p C) in water environment becoming a challenge in the treatment processes. Herein, the synchronous photocatalytic reduction of Cr(VI) and oxidation of p C by silver oxide decorated on fibrous silica zirconia (AgO/FSZr) was reported. In this study, the catalysts were successfully developed using microemulsion and electrochemical techniques with various AgO loading (1, 5 and 10 wt%) and presented as 1, 5 and 10-AgO/FSZr. Catalytic activity was tested towards simultaneous photoredox of hexavalent chromium and p -cresol (Cr(VI)/ p C) and was ranked as followed: 5-AgO/FSZr (96/78%) > 10-AgO/FSZr (87/61%) > 1-AgO/FSZr (47/24%) > FSZr (34/20%). The highest photocatalytic activity of 5-AgO/FSZr was established due to the strong interaction between FSZr and AgO and the lowest band gap energy, which resulted in less electron-hole recombination and further enhanced the photoredox activity. Cr(VI) ions act as a bridge between the positive charge of catalyst and cationic p C in pH 1 solution which can improve the photocatalytic reduction and oxidation of Cr(VI) and p C, respectively. The scavenger experiments further confirmed that the photogenerated electrons (e − ) act as the main species for Cr(VI) to be reduced to Cr(III) while holes (h + ) and hydroxyl radicals are domain for photooxidation of p C. The 5-AgO/FSZr was stable after 5 cycles of reaction, suggesting its potential for removal of Cr(VI) and p C simultaneously in the chemical industries. Graphical abstract: Image 1 Highlights: AgO is the major phase decorated on fibrous silica zirconia (FSZr). Well AgO loading on FSZr induced the interaction of Si–O–Ag. The interplay of FSZr and AgO greatly reducing the electron-hole recombination. 5-AgO/FSZr showed the highest simultaneous photoredox of Cr(VI) and p -cresol (pC). e −, h + and OHads are the active species in simultaneous photoredox of Cr(VI) and p C.